The life and times of the thunderbolt kid : a memoir - Bryson, Bill (New York : Broadway Books, 2006)
Like millions of his generational peers, Bill Bryson grew up with a rich fantasy life as a superhero. Using his fantasy-life persona as a springboard, Bryson re-creates the life of his family in the 1950s in all its transcendent normality--a life at once familiar to us all and as far away and unreachable as another galaxy.--From publisher description.
Includes bibliographical references (p. [269]-270)
Keywords: Bryson, Bill -- Childhood and youth; Travel writers -- United States -- Biography; Des Moines (Iowa) -- Biography